2014
DOI: 10.1208/s12249-014-0166-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Granulated Lactose as a Carrier for DPI Formulations 1: Effect of Granule Size

Abstract: ABSTRACT. The objective of this study was to investigate the effect of large granulated lactose carrier particle systems on aerosol performance of dry powder inhaler formulations. Granulated lactose carriers with average sizes ranging from 200 to 1,000 μm were prepared and subsequently fractionated into separate narrow size powders. The fractionated granulated lactose (GL) samples were characterized in terms of size, specific surface area, surface roughness, morphology, density, flowability, and solid-state. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Decreasing the size of carrier particles was shown to lead to increased [18,41,61,81,130,[140][141][142][143][144][145][146][147], decreased [135,143,144], and similar [64,80,[148][149][150][151][152][153] FPFs of drug. This is because the degree by which carrier size affects the dispersion of a DPI formulation is influenced by other interacting variables such as the type of drug [154], type of inhaler [144], the chemical nature of carrier [155], and the amounts of fine excipient additives [156].…”
Section: Size Distributionmentioning
confidence: 99%
“…Decreasing the size of carrier particles was shown to lead to increased [18,41,61,81,130,[140][141][142][143][144][145][146][147], decreased [135,143,144], and similar [64,80,[148][149][150][151][152][153] FPFs of drug. This is because the degree by which carrier size affects the dispersion of a DPI formulation is influenced by other interacting variables such as the type of drug [154], type of inhaler [144], the chemical nature of carrier [155], and the amounts of fine excipient additives [156].…”
Section: Size Distributionmentioning
confidence: 99%
“…23 Recently, carriers with a large size fraction (>200 mm), especially with significantly rough surfaces, have shown improved aerosol performance. 5,24 This improvement is explained by the switch of the predominant detachment mechanism from turbulence flow to impaction force. 5 Meanwhile, on account of the extremely small cohesive force/weight ratio, these large carrier particles exhibited better flow properties than their smaller counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study found that significantly larger granulated lactose with super macro roughness improves uniformity and aerosol performance when using a low dose of model drug. 24 Super macro roughness was defined by the distance between 2 rough peaks being 1000 times larger than the size of drug particle. Contrary to macro roughness, the super rough surface of the large granulated lactose carriers actually improved aerosol performance by sheltering more drug particles from press-on forces better than their smooth counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations